C0044 Ultrasound-guided gastrocnemius recession: a new ultra–minimally invasive surgical technique. (5th July 2018) - Villanueva, Manuel; Iborra, Alvaro; Sanz, Pablo; Fabian, Guillermo Rodriguez
Abstract : Background: Isolated gastrocnemius contracture is thought to lead to numerous foot and ankle pathologic conditions. Gastrocnemius equinus is typically defined as ankle dorsiflexion <10° with the knee extended. The gastrocnemius recession like technique has many well-documented indications. It is considered indicated in adults with dorsiflexion <10° with the knee extended. The aim of this study was to evaluate the safety and efficacy of a new technique based on ultrasound-guided ultra–minimally invasive gastrocnemius recession. Methods: We performed gastrocnemius recession in 23 patients, 18 males and 5 females. Mean age was 42 years (13–61). The patients with equinus foot were aged 13, 14, and 15 years. The age range of patients with Achilles tendinopathy or plantar fasciitis was 37–51 years. The age range of patients with metatarsalgia was 50–61 years. All patients had previously received multiple treatments and had at least 6 months of conservative management prior to surgery. However, their symptoms failed to resolve. The average duration of symptoms ranged from 1 to 5 years. Results: Surgical technique: recession is performed via a single 1–2–mm incision. Occasionally, 2 incisions are required to follow the shape of the gastrocnemius and complete the resection. As the anaesthesia is local, the patient can then actively flex the foot dorsally and plantar shortly after the procedure. No stitches are required. Complications: all patients developed mild superficial hematomas that resolved in 3–4 weeks. These were worse in patients with non-insertional Achilles tendinopathy. Four patients experienced slight weakness, which resolved at 6 months. Conclusions: All the procedures were performed under local anaesthesia plus sedation in an outpatient regimen, without lower limb ischemia No sutures were necessary. A key advantage of our approach is the possibility of combining ultrasound-guided ultra–minimally invasive techniques to ensure minimal pain with excellent outcomes and no significant morbidity. Ultrasound-guided, ultra–minimally invasive surgery is an emerging technology that gives the surgeon direct control over the main structures and may be the future gold-standard for many surgical procedures such as plantar fasciotomy, gastrocnemius recession, and treatment of non-insertional Achilles tendinopathy. However, the learning curve is steep, because the surgeon has to perfect the technique with cadavers and become competent in the use of ultrasound.